Evaluation of a Pretargeting Strategy for Molecular Imaging of the Prostate Stem Cell Antigen with a Single Chain Antibody - Tienken, Lena (Sci Rep, 2018)
In pretargeted radio-immunotherapy, the gradual administration of a non-radioactive tumor antigen-addressing antibody-construct and the subsequent application of a radioactive labeled, low molecular weight substance enable a highly effective and selective targeting of tumor tissue. We evaluated this concept in prostate stem cell antigen (PSCA)-positive cancers using the antigen-specific, biotinylated single chain antibody scFv(AM1)-P-BAP conjugated with tetrameric neutravidin. To visualize the systemic biodistribution, a radiolabeled biotin was injected to interact with scFv(AM1)-P-BAP/neutravidin conjugate. Biotin derivatives conjugated with different chelators for complexation of radioactive metal ions and a polyethylene glycol linker (n = 45) were successfully synthesized and evaluated in vitro and in a mouse xenograft model. In vivo, the scFv(AM1)-P-BAP showed highly PSCA-specific tumor retention with a PSCA(+) tumor/PSCA(-) tumor accumulation ratio of ten. PEGylation of radiolabeled biotin resulted in lower liver uptake improving the tumor to background ratio.